Trust and Networking as Elements of Social Capital During Fieldwork in Malaysia to Mitigate Methodological Obstacles: A Bangladeshi Overview - Bushra Zaman (The Malaysian Journal of Social Administration, 2025)
This paper examines the roles of trust and networking in overcoming fieldwork challenges in Malaysia. The obstacles and their management were described using a phenomenological methodology. Among the most challenging aspects of fieldwork are gender stereotypes, language barrier, safety and security of the researcher, the inherent unpredictability of migrant workers, and the initial rejection of the primary informants. Data was successfully collected from Indonesian and Bangladeshi migrant workers by creating and strengthening networks, building relationships as a means of bonding with people from the same country, achieving acceptance, and exploring alternative means of addressing the different challenges being endured and organised. Despite the unpredictability of fieldwork, the findings demonstrated that impediments can be reduced through the active participation of researchers in identifying risks and developing strategies to mitigate them. Two essential components of social capital — trust and networking — played a crucial role in overcoming fieldwork obstacles. This article describes the researcher's fieldwork experiences and how the elements of social capital, trust and networking are utilised to overcome obstacles. This paper aims to contribute to the reduction of methodological obstacles and the development of a risk management strategy for future researchers, particularly female researchers in a foreign country, by sharing practical experiences and challenges and empowering them in their research endeavours.